Repayment of EU Bailout Loans in a Member-Country of the ES: The Case of Greece - Vasiliki Dimakopoulou; George Economides; Apostolis Philippopoulos (CESifo GmbH, 2024)
This paper quanti.es the future implications of repayment of bailout loans received by Greece from the EU in the previous decade. These debt obligations amount today to 240 billion euros or 70% of the country's total public debt and have to be repaid by 2070. This is investigated in a dynamic general equilibrium model calibrated to the Greek economy, in which fiscal policy is conducted under the rules of the new fiscal governance framework and quantitative monetary policy is subject to the rules of the Eurosystem. Our simulations show that, other things equal, repayment will have recessionary implications in the years to come, although the magnitude of these unpleasant implications will depend on how much privately-held public debt rises as the EU-held public debt falls. We then search for ways to mitigate these recessionary effects. While NGEU/RRF funds as they take place at the moment, as well as a new hypothetical support from the ES in the form of more quantitative easing are found to have small and/or temporary ben-eficial effects only, our simulations show that what can really help is an improvement in total factor productivity.
Keywords: F34; E62; E42; 330; international loans; fiscal policy; monetary regimes